Upaya Peningkatan Hasil Belajar Materi Tolak Peluru Melalui Media Modifikasi Bola Plastik Isi Pasir Siswa SMPN 11 SURABAYA Tahun Ajaran 2023/2024 - Mochammad Nadian Hulaimi; Bambang Ferianto Tjahyo Kuntjoro; Ciciek Ismayadewi (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The aim of this research is to explain how to use plastic balls filled with sand to improve the ability of students at SMPN 11 Surabaya in Semampir District, Surabaya City in shot put. Classroom action research is the subject of this research. Planning, action, observation/evaluation, and reflection are the steps taken to obtain accurate information. This research involved in 1st grade students at SMPN 11 Surabaya. The data collection method used was observation and shot put tests with a back to back and side to side shot. Data analysis involves reducing data, conveying data, and drawing conclusions. The results of the research show that using plastic balls filled with sand can improve the ability of 1st grade students at SMPN 11 Surabaya in shot put. This is proven by the increase in shot put learning outcomes before being given action with a low category/score increasing to a high category.